Edukasi Tentang Praktik Personal Hygiene pada Wanita di PMB Nislawati Ridan Permai, Kecamatan Bangkinang Kabupaten Kampar 2025: Penelitian - Erma Kasumayanti; Endang Mayasari; Siti Hotna; Nislawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Personal hygiene is an important aspect in maintaining health, especially for mothers who are in the reproductive phase or who have toddlers. Good hygiene practices not only contribute to an individual's health, but significantly impact the health of their children. One of the key factors influencing personal hygiene practices is the mother's knowledge about the importance of cleanliness. The aim of health education regarding personal hygiene practices is; to increase mothers' knowledge about personal hygiene, prevent disease and infection, increase independence and self-confidence, encourage behavior change and build social support. Community Service activities are carried out using lecture and demonstration methods. Based on the results of the evaluation of this service activity, it is known that of the 20 mothers classified as Women of Childbearing Age, 90% really understood the material presented. The activity participants were very enthusiastic about the material provided. Participants were able to answer questions during the evaluation after the health education activities were carried out. It is hoped that mothers can improve their personal hygiene practices so that they have a positive impact on the health of individuals and their families.